The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7763/ijet.2015.v7.799
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Process Analysis in a DISI Engine Fuelled with N-Butanol through UV-VIS Emission Spectroscopy

Abstract: Abstract-In this paper, the study on the effects of n-butanol on the combustion process in a DISI engine has been conducted.Experiments were performed on a direct injection SI engine operated on gasoline and butanol, with combined analysis of in-cylinder pressure traces, exhaust emissions and optical data. The optically accessible power unit was fitted with a commercial head and a high pressure wall guided injection system working at 100 bar. The engine speed was set at 2000 rev/min as a representative value f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…N 2 * can emit weakly at ~316 nm and ~337 nm due to C 3 Π→B 3 Π (0, 1) and (0, 0) transitions. In addition, N 2 + emission can be characterized due to transitions in the 330-435 nm range [36,37,38]. However, it has been noted that the emissions of N 2 * and N 2 + can be very unstable [38,39].…”
Section: Emissions Spectra During Combustionmentioning
confidence: 99%
See 2 more Smart Citations
“…N 2 * can emit weakly at ~316 nm and ~337 nm due to C 3 Π→B 3 Π (0, 1) and (0, 0) transitions. In addition, N 2 + emission can be characterized due to transitions in the 330-435 nm range [36,37,38]. However, it has been noted that the emissions of N 2 * and N 2 + can be very unstable [38,39].…”
Section: Emissions Spectra During Combustionmentioning
confidence: 99%
“…In addition, N 2 + emission can be characterized due to transitions in the 330-435 nm range [36,37,38]. However, it has been noted that the emissions of N 2 * and N 2 + can be very unstable [38,39]. During combustion, chemical reactions in the flame generate excited species (OH*, CH*, C 2 * and CO 2 *), which are the main chemiluminescent emitters in hydrocarbon flames.…”
Section: Emissions Spectra During Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of ethanol/gasoline blends impact on performance and emissions of a spark-ignited engine is given in [8][9][10][11][12][13][14][15][16]. In [17][18][19][20][21][22][23][24][25][26] results are given concerning the use of butanol, either blended with gasoline or as a neat fuel, in a spark-ignited engine. By observing these results, it can generally be concluded that the increase in alcohol content in the blend with gasoline, could have a significant impact on engine performance and efficiency only at high alcohol concentrations, if the air-fuel ratio is to be maintained within the same range of values as for the gasoline operation.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, many of the theoretical and experimental studies evaluating the potential of alcohols are based on ethanol [8][9][10][11][12][13][14][15][16], while other studies have been performed on butanol-fueled engines [17][18][19][20][21], or on assessing n-butanol as a blending agent with gasoline [22][23][24][25][26]. Ethanol can be used as a neat fuel in spark-ignited engines or blended up to 40% with diesel fuel for use in compression-ignition (CI) engines [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%